El modelo de interculturalidad en el informe de la Comisión Bouchard-Taylor para Québec - Elósegui Itxaso, María (Anuario de Derechos Humanos. Nueva Época, 2010)
This article studies the legal intercultural model and its relation with human rights, elaborated by Charles Taylor and Gérard Bouchard in the report Building the future. A time for reconciliation, published in Québec in 2008 and some of the possible legal applications in Spain.